Development of a modular MR valve using meandering flow path structure - Ichwan, Burhanuddin (Institute of Physics Publishing, 2016)
The extensive development of the magnetorheological (MR) valve has successfully introduced a new high-performance compact-class MR valve using a meandering flow path structure. Aside from the performance improvement, in real applications, the ease of performance adjustment also needs to be improved. This study focused on the development of a new design of a modular MR valve using a meandering flow path to improve the adjustability of the valve performance. The approach is proposed based on the high-performance advantages of a meandering flow path structure, while at the same time utilizing the benefit of the modular structure in terms of performance flexibility. In order to evaluate the performance of the modular structure, the analytical assessment was conducted for three different module stages: the single-stage module, the double-stage module, and triple-stage module. To predict the strength of the magnetic field in the effective area, the magnetic simulation was conducted through an open-source software called the FEMM (Finite Element Method Magnetics). The quasi-steady mathematical model of the proposed valve was also derived to conduct the analytical assessment as well as to predict the valve performance. In order to validate the simulation results, the prototypes of the proposed valve are experimentally tested with the aid of the hydraulic cylinder on a dynamic test machine. The results of the MR valve assessment from both the simulation and experimental test demonstrated that the pressure drop rating of the meandering type MR valve can be easily modified using modular structure by changing the number of module stages.